2020
DOI: 10.1038/s41598-020-62096-7
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelium Cell Density and Bruch’s Membrane Thickness in Secondary versus Primary High Myopia and Emmetropia

Abstract: To assess differences between secondary high myopia (SHM) due to congenital glaucoma and primary high myopia (PHM) and non-highly myopic eyes (NHM) in the relationships between axial length and Bruch's membrane (BM) thickness and retinal pigment epithelium (RPE) density. The histomorphometric study included human globes enucleated for reasons such as malignant uveal melanoma, end-stage painful secondary angle-closure glaucoma and congenital glaucoma. BM thickness and RPE cell density were measured upon light m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…PM is characterised by increased AL, accompanied by pathological or degenerative changes in the neurosensory retina, RPE, choroid and sclera, resulting in the progression of myopic maculopathy and subsequent visual impairment. Previous studies showed that decreased density of the RPE might be associated with the pathogenesis of PM 29. In this study, PSMD3 was found highly expressed in the HRPE layer.…”
Section: Discussionsupporting
confidence: 62%
“…PM is characterised by increased AL, accompanied by pathological or degenerative changes in the neurosensory retina, RPE, choroid and sclera, resulting in the progression of myopic maculopathy and subsequent visual impairment. Previous studies showed that decreased density of the RPE might be associated with the pathogenesis of PM 29. In this study, PSMD3 was found highly expressed in the HRPE layer.…”
Section: Discussionsupporting
confidence: 62%
“…It holds true in particular for regional differences in the decrease of the photoreceptor density with longer axial length. The thickness of the whole retina was examined in a previous small-scaled histological study in which the retinal inner nuclear layer and outer nuclear layer, assessed at the equator and in the midperiphery, decreased in thickness with longer axial length 7 , 20 . The RPE cell density in relationship to axial length has recently been addressed in another study which as the present investigation found that the RPE cell density decreased with longer axial length in the midperiphery and at the equator, while in that study, the RPE cell density measured in the ora serrata region was not significantly correlated with axial length 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the fundus periphery in the retro-equatorial and equatorial region, the density of the RPE and the thickness of the retina decreased with longer axial length [16,17]. Again, in contrast to globes with primary myopia, eyes with secondary high myopia due congenital glaucoma showed a decreasing density of the macular RPE cells with longer axial length [14,18].…”
Section: Bruch's Membranementioning
confidence: 96%